FORMATION OF COMMUNICATIVE COMMUNICATION OF SCHOOL-AGE CHILDREN WITH AUTISM - Akhmedova Saida Jamiliddin qizi (Web of Journals Publishing, 2025)
This article provides valuable information about various approaches to the formation of communicative communication in school-age children with a diagnosis of autism.
Keywords: Autism, communication, behavior, socialization, developmental technologies, school, principle, communication, phonemic perception, emotional stimulation, social stories, social skills, special education.